2014
DOI: 10.1371/journal.pone.0093155
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Fate of Double-Stranded RNA in Agricultural Soils

Abstract: A laboratory soil degradation study was conducted to determine the biodegradation potential of a DvSnf7 dsRNA transcript derived from a Monsanto genetically modified (GM) maize product that confers resistance to corn rootworm (CRW; Diabrotica spp.). This study provides new information to improve the environmental assessment of dsRNAs that become pesticidal through an RNAi process. Three agricultural soils differing in their physicochemical characteristics were obtained from the U.S., Illinois (IL; silt loam), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(151 citation statements)
references
References 37 publications
10
135
2
4
Order By: Relevance
“…Likewise, when maize seedlings were irrigated with dsRNA of Kunitz-type trypsin inhibitors (dsKTI), this resulted in a high mortality rate with the Asian corn borer, Ostrinia furnacalis (Li et al, 2015a). Although interesting, Dubelman et al (2014) reported that the soil persistency of dsRNA can be short, with a rapid breakdown within 2–3 days. Therefore, the dsRNA stability in the soil is still a matter of question.…”
Section: Novel Delivery Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, when maize seedlings were irrigated with dsRNA of Kunitz-type trypsin inhibitors (dsKTI), this resulted in a high mortality rate with the Asian corn borer, Ostrinia furnacalis (Li et al, 2015a). Although interesting, Dubelman et al (2014) reported that the soil persistency of dsRNA can be short, with a rapid breakdown within 2–3 days. Therefore, the dsRNA stability in the soil is still a matter of question.…”
Section: Novel Delivery Methodsmentioning
confidence: 99%
“…Supply of dsRNA through irrigation water, root drench, or trunk injection would be a great strategy for pest insects, such as root feeders, for which no efficient control method is available at this moment. Moreover, the delivery of dsRNA through irrigation or trunk injections holds low environmental risks due to the rapid breakdown of dsRNAs within 2–3 days in the soil and plant debris (Petrick et al, 2013; Dubelman et al, 2014), as well as due to the localized application fashion.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Many different delivery approaches have been used for per os RNAi trigger delivery in larvae, including naked dsRNA in buffer or water [126,127]. Although naked dsRNA can be internalized at high concentration in sterile conditions in the lab, dsRNA in field settings could be subject to rapid environmental degradation [21,22]. To prevent RNAi trigger degradation, abiotic and biotic delivery systems including the use of Effectene ® (Qiagen) liposomes, chitosan nanoparticles, E. coli expression systems, and Pichia pastoris expression systems have been explored [27,47,49,75,122,123,128,129].…”
Section: Rnai Triggers With Potential Mosquito Control Applicationsmentioning
confidence: 99%
“…In order to achieve these same detrimental phenotypes in wild populations, RNAi triggers must be delivered to the target species and life stage with consideration for environmental and abiotic factors including: UV, ribonucleases, microbes, dissipation and dilution in aqueous environs and on solid substrates [20,21,22,23]. RNAi triggers must also be delivered to target mosquito species using field feasible applications.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, the transgenic nature of HIGS and its mode of action have been under considerable scrutiny [98][99][100]. The environmental persistence of dsRNAs in agricultural soils has been explored and found to be low, reducing the chance of off-target effects [101]. Already, a few field crop varieties with effective antiviral HIGS have been approved and widely grown [102].…”
Section: Box 2 Field Control Of Plant Pathogenic Fungi By Rna-based mentioning
confidence: 99%